The role of viable but non-infectious developmental forms in chlamydial biology - Alan Paul Hudson (Frontiers Research Topics, 2014)
The chlamydiae are Gram-negative, obligate intracellular bacteria with a complex developmental cycle comprising a metabolically less-active, infectious stage, the elementary body (EB), and a metabolically more active stage, the reticulate body (RB). They are responsible for many acute and chronic diseases in humans and animals. In order to play a causative role in chronic diseases, chlamydiae would need to persist and to re-activate within infected cells/tissues for extended periods of time. Persistence in vitro is defined as viable but non-cultivable chlamydiae involving morphologically enlarged, aberrant, and nondividing RBs, termed aberrant bodies (AB). In vitro, alterations of the normal developmental cycle of chlamydiae can be induced by the addition of Interferon-? (IFN-?), tumor necrosis factor-a (TNF-a) and penicillin G exposure as well as amino acid or iron deprivation, monocyte infection and co-infection with viruses. In vivo, key questions include whether or not ABs occur in infected patients and animals and whether such ABs can contribute to prolonged, chronic inflammation, fibrosis, and scarring through continuing stimulation of the host immune system known from diseases such as trachoma, pelvic inflammatory disease, reactive arthritis and atherosclerosis. To date, the direct causal role in the pathogenesis of chlamydial infection and persistence in vivo has been questioned since there was no tractable animal model of chlamydial persistence so far. A very recent study was able to establish an experimental animal model of in vivo persistence, when C. muridarum vaginally-infected mice were gavaged with amoxicillin. Amoxicillin treatment induced C. muridarum to enter the persistent state in vivo. Recent in vivo data from patients indicate that viable but non-infectious developmental stages are present in the genital tract of chronically-infected women and that the gastrointestinal tract might be a reservoir for persistent chlamydial infections at other sites.